2009
DOI: 10.1016/j.jce.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Do China and oil exporters influence major currency configurations?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…It is, in particular, advanced country currencies, and foremost the euro and currencies that are managed vis-a-vis the euro, which are influenced by changes to the RMB regime. This finding is consistent with an earlier study (Fratzscher and Mehl, 2009)which focused, however, on the US dollar, euro and yen onlythat had shown that expectations of a weakening of the RMB peg to the US dollar trigger a re-balancing of portfolios into other reserve currencies, such as the euro. As a consequence, the largest effect of those statements is found for currencies that rely on the euro as an anchor, possibly due to market expectations of diversification of China's reserves out of the US dollar into the euro, along with that of a possibly declining dominance of the US currency in the international monetary system.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…It is, in particular, advanced country currencies, and foremost the euro and currencies that are managed vis-a-vis the euro, which are influenced by changes to the RMB regime. This finding is consistent with an earlier study (Fratzscher and Mehl, 2009)which focused, however, on the US dollar, euro and yen onlythat had shown that expectations of a weakening of the RMB peg to the US dollar trigger a re-balancing of portfolios into other reserve currencies, such as the euro. As a consequence, the largest effect of those statements is found for currencies that rely on the euro as an anchor, possibly due to market expectations of diversification of China's reserves out of the US dollar into the euro, along with that of a possibly declining dominance of the US currency in the international monetary system.…”
supporting
confidence: 92%
“…We found that the parameter estimates doubled from −0.10 before 2005 to almost −0.20 after 2005. In other words, a statement pointing to relaxation of China's peg to the US dollar or to diversification of China's reserves away from the US dollar leads to an appreciation of emerging Asian currencies of 0.2% on average vis‐à‐vis the US dollar, on the day the statement occurs (a magnitude comparable with that found by Fratzscher and Mehl () for the euro and the yen against the dollar).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations